Analysis of dengue virus burden and serotypes pattern in Faisalabad, 2016–2017. (23rd February 2018) - Yousaf, Muhammad; Junaid, Kashaf; Iqbal, Muhammad Sarfaraz; Aslam, Imran; Ahmad, Sheraz; Aqeel, Muhammad; Ashfaq, Usman Ali; Khaliq, Saba; Ghani, Muhammad Usman; Waqar, Nayyar
Dengue is the fastest growing mosquito-borne viral infection and has become a public epidemic in Pakistan. This cross-sectional study was carried out to explore the prevalence and characterization of dengue virus serotypes in Faisalabad, Pakistan during 2016–2017.Aim: To determine most prevalent dengue serotype in Faisalabad, Pakistan.Methodology: Cross-sectional study of stored serum specimens for dengue virus genotype by multiplex real time (RT)-PCR, antidengue IgM, IgG and NS1.Results: Viral RNA detection of 42 patients revealed positive results in 125 (34.4%) samples. DENV-3 (76%) was the predominant genotype followed by DENV-2 (17%) and 7% of DENV1. None of the samples were positive for DENV-4.Conclusion: DENV-3 is the most prevalent serotype of dengue virus observed in Faisalabad, Pakistan.